Impact of prostate cancer testing: an evaluation of the emotional consequences of a negative biopsy result. - Macefield, R; Metcalfe, C; Lane, J; Donovan, J; Avery, K; Blazeby, J; Down, L; Neal, D; Hamdy, F; Vedhara, K (2010)
BACKGROUND: When testing for prostate cancer, as many as 75% of men with a raised prostate-specific antigen (PSA) have a benign biopsy result. Little is known about the psychological effect of this result for these men. METHODS: In all, 330 men participating in the prostate testing for cancer and treatment (ProtecT) study were studied; aged 50-69 years with a PSA level of > or = 3 ng ml(-1) and a negative biopsy result. Distress and negative mood were measured at four time-points: two during diagnostic testing and two after a negative biopsy result. RESULTS: The majority of men were not greatly affected by testing or a negative biopsy result. The impact on psychological health was highest at the time of the biopsy, with around 20% reporting high distress (33 out of 171) and tense/anxious moods (35 out of 180). Longitudinal analysis on 195 men showed a significant increase in distress at the time of the biopsy compared with levels at the PSA test (difference in Impact of Events Scale (IES) score: 9.47; 95% confidence interval (CI) (6.97, 12.12); P<0.001). These levels remained elevated immediately after the negative biopsy result (difference in score: 7.32; 95% CI (5.51, 9.52); P<0.001) and 12 weeks later (difference in score: 2.42; 95% CI (0.50, 1.15); P=0.009). Psychological mood at the time of PSA testing predicted high levels of distress and anxiety at subsequent time-points. CONCLUSIONS: Most men coped well with the testing process, although a minority experienced elevated distress at the time of biopsy and after a negative result. Men should be informed of the risk of distress relating to diagnostic uncertainty before they consent to PSA testing.